Life cycle sustainability assessment of electrified road systems. (30th April 2019) - Balieu, R.; Chen, F.; Kringos, N.
Abstract : The widespread use of Electric Vehicles (EVs) has been one of the main directions for pursuing a sustainable future of road transport in which the deployment of the associated charging infrastructures, static or dynamic, has been included as one of the main cornerstones for its success. Different electrified road (eRoad) systems which allow for dynamic charging of EVs by transferring electrical power from the road to the vehicle in-motion, either in a conductive or contactless way, are under active investigation. One of the important tasks in feasibility analysis of such infrastructure is to quantitatively assess its environmental performance and, thus, the consequential influences to the sustainability of road electrification as a whole. Having this concern in mind, in this study, a systematic LCA study is carried out in which the environmental impacts from the different life cycle stages have been calculated and compared among several promising eRoad systems. In a next step, suitable strategies can be accordingly made to minimise these impacts in a most effective way; and more importantly, the LCA results of this study can serve as one of the important bases for conducting a more comprehensive and objective evaluation of the potential environmental benefits EVs could bring.